Destination anywhere - Barnard, Sara; e rtist.9 (2021)
"Peyton King has always wanted to belong. She seizes the opportunity to start over at a new school and finally finds real connections with the friends she's always dreamed of and even an actual boyfriend! But after flying high in her newfound happiness, Peyton comes crashing down when reality sets in and the ones she cares about let her down. Peyton's friends can't fix her and she can't help them if they won't let her. If she wants to find real, lasting happiness, Peyton will have to search somewhere else. With nothing but her sketchpad and a backpack, she buys a one-way ticket and gets on a plane. How far will she go to change her story?"--Amazon.com.
"A novel."--Page [1] of jacket cover.
HL760L
Keywords: College students -- Fiction; Friendship -- Fiction; Change (Psychology) -- Fiction; Drug abuse -- Fiction; Social acceptance -- Fiction; British -- Canada -- Fiction; Young adult fiction; High schools -- Fiction; Schools -- Fiction; Coming of age -- Fiction; Bildungsromans; Road fiction